Identifying the Motivation of Indonesian Muslim Women in Traveling - Christin Susilowati; Rila Anggraeni; Moh Athoillah (Asia Pacific Journal of Management and Education (APJME), 2024)
Several studies have been conducted to evaluate the tourism industry, but very little is known about Muslim travel, particularly that of Muslim women. The motivation of Muslim women to travel is one issue that needs to be investigated, as it represents a potential target market that has not received adequate attention. This study aims to pinpoint Indonesian Muslim women's travel-related motivations. The study used a qualitative approach by conducting semi-structured interviews with nineteen Muslim women respondents chosen from a wide range of backgrounds. The interview guide consisted of questions separated into two primary categories: travel and socio-demographic profile. The results showed four primary motivations driving Muslim women to travel: (1) Spiritual growth (appreciating God's creation, receiving a blessing from God, learning about the beauty of God's creation, and showing gratitude to God); (2) Seeking experiences; (3) Destination allure; and (4) Self-relieving. The findings suggest that tourist providers must design goods and services that cater to the needs of Indonesian Muslim women.